2003
DOI: 10.1111/1467-9922.00212
|View full text |Cite
|
Sign up to set email alerts
|

Attitudes, Motivation, and Second Language Learning: A Meta–Analysis of Studies Conducted by Gardner and Associates

Abstract: This meta-analysis investigates the relationship of second language achievement to five attitude/motivation variables from Gardner's socioeducational model: integrativeness, attitudes toward the learning situation, motivation, integrative orientation, and instrumental orientation. These relationships were examined in studies conducted by Gardner and associates using the Attitude/Motivation Test Battery and various measures of second language achievement including self-ratings, objective tests, and grades. In t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

20
380
2
26

Year Published

2011
2011
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 597 publications
(428 citation statements)
references
References 42 publications
20
380
2
26
Order By: Relevance
“…Many authors have found a positive correlation between motivation and foreign language attainment (e.g., Schmidt and Watanabe, 2001;Masgoret and Gardner, 2003;Csizér and Dörnyei, 2005;Bernaus and Gardner, 2008;Yu and Watkins, 2008). This type of studies have examined the relationship between types of motivation and foreign language learning by paying attention to variables such as age or gender.…”
Section: Motivation Towards Foreign Languagementioning
confidence: 99%
“…Many authors have found a positive correlation between motivation and foreign language attainment (e.g., Schmidt and Watanabe, 2001;Masgoret and Gardner, 2003;Csizér and Dörnyei, 2005;Bernaus and Gardner, 2008;Yu and Watkins, 2008). This type of studies have examined the relationship between types of motivation and foreign language learning by paying attention to variables such as age or gender.…”
Section: Motivation Towards Foreign Languagementioning
confidence: 99%
“…A number of studies including those carried out by Gardner and his colleagues have argued that language learning motivation is a key factor of successful language learning (see e.g. Masgoret and Gardner (2003) for more reviews of this literature). Accordingly, motivated students would be more eager and enthusiastic to devote the time required to language learning.…”
Section: Introductionmentioning
confidence: 99%
“…Gardner and Lambert have established the most commonly used framework for understanding the different attitudes and motivation that language learners typically have. Gardner's (1985) particular, quite narrow, use of the term motivation has required clarification, which Masgoret and Gardner (2003) provided by distinguishing between orientations and motivation. Masgoret and Gardner have contended that motivation is mainly goal-directed behavior, revealed in a variety of more specific behaviors and cognitions that serve as the manifestations of motivation.…”
Section: Introductionmentioning
confidence: 99%
“…Dörnyei, 2003;Masgoret & Gardner, 2003), the Turkish group shows a clear tendency to present mainly pragmatic and instrumental reasons to learn Portuguese, whereas the Portuguese group shows a tendency to present mainly integrative and affective reasons to learn Turkish (see Table 3). …”
Section: Participantsmentioning
confidence: 99%